2022
DOI: 10.1038/s41598-022-22516-2
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perception of interpersonal coordination during joint painting

Abstract: Interpersonal coordination is important for many joint activities. A special case of interpersonal coordination is synchronization, which is required for the performance of many activities, but is also associated with diverse positive social and emotional attributes. The extent to which these effects are due to the reliance on synchrony for task performance or to its specific rhythmic characteristics, is not clear. To address these questions, we considered a more general form of interpersonal coordination, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Our finding that children perceive synchronized partners as higher in affiliation than asynchronous partners is consistent with previous research into the influence of witnessed IS on children's social judgements (Abraham et al, 2022;Cirelli et al, 2018;Fawcett & Tunçgenç, 2017). In previous studies, participants visually observed the target interactions and the context in which they took place.…”
Section: Is As a Social Heuristic In Childrensupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that children perceive synchronized partners as higher in affiliation than asynchronous partners is consistent with previous research into the influence of witnessed IS on children's social judgements (Abraham et al, 2022;Cirelli et al, 2018;Fawcett & Tunçgenç, 2017). In previous studies, participants visually observed the target interactions and the context in which they took place.…”
Section: Is As a Social Heuristic In Childrensupporting
confidence: 91%
“…In previous studies, participants visually observed the target interactions and the context in which they took place. For example, one previous study involved teddy bears moving either synchronously or asynchronously and 'talking' with each other (Fawcett & Tunçgenç, 2017), and another involved a child and adult engaged side-by-side in a painting activity using either synchronous or asynchronous movements (Abraham et al, 2022). Ours was a socially 'lean' paradigm in comparison: the brief (11.5s) interactions on which affiliation judgements were based included no visual movement information and minimal social contextual information.…”
Section: Is As a Social Heuristic In Childrenmentioning
confidence: 99%
See 1 more Smart Citation